Low turbidity water treated with seeds of Moringa oleífera Lam. - Nascimento, Amanda Caroline Santos; Oliveira, Alden Felipe Guimarães de; Lavôr, Maísa Barbosa de; Pereira, Elionaide Carmo; Amorim, Miriam Cleide Cavalcante de (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2020)
Effective and affordable solutions are being researched to reduce the problems generated by water scarcity in rural communities. Moringa is a natural polymer composed of cationic proteins, which are highlighted as a coagulant in the treatment of water for human consumption. Thus, the objective was to find the best concentration values for the removal of color and turbidity and sedimentation time, thus evaluating the power of Moringa seeds in the removal of Escherichia coli (E. coli) and heterotrophic bacteria in waters of low turbidity, since it does not perform well. The dosages used were 500, 600, 800 and 1000 mg L-1 and the sedimentation times tested were between 18 and 90 minutes. The best values of color removal and turbidity were found with lower dosages, because it is low turbidity water, resulting in the ideal contraction of 500 mg L-1. The minimum sedimentation time for maximum clarification efficiency was 90 minutes. Finally, after the definition of the dosage and better sedimentation time, removals of up to 29% for E. coli and 66% for heterotrophic bacteria were obtained, being within the parameters of potability for water for human consumption.